Analisis Akuntabilitas dan Transparansi pada Organisasi Pengelola Zakat dalam Memaksimalkan Potensi Zakat - Ruslan Abdul Ghofur; Suhendar Suhendar (ITB AAS INDONESIA Surakarta, 2021)
This research is motivated by the low realization of zakat collection because muzakki still have doubts about the existence of BAZ or LAZ, in distributing zakat to those who are entitled. This study aims to analyze the Accountability and Transparency of the Zakat Management Organization in Maximizing the Potential of Zakat. Accountability is realized by the presence of transaction evidence and witnesses during the recording process in the management of zakat funds. Meanwhile, transparency is a principle that gives freedom and guarantees everyone to get information related to the organization of the organization. This research uses a qualitative field approach based on qualitative descriptive. The data sources in this study are primary data and secondary data. This research was conducted approximately one year from June 2019 - July 2020. The data collection techniques in this study were interviews, structured interviews, semi-structured interviews and unstructured interviews. Data analysis techniques in this study were data reduction, data exposure and conclusion drawing. The results showed that BAZNAS Lampung and Banten Provinces were accountable and transparent in managing Zakat funds.